2007
DOI: 10.1002/eqe.724
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration response modification factors for nonstructural components attached to inelastic moment‐resisting frame structures

Abstract: A statistical analysis of the peak acceleration demands for nonstructural components (NSCs) supported on a variety of stiff and flexible inelastic regular moment-resisting frame structures with periods from 0.3 to 3.0 s exposed to 40 far-field ground motions is presented. Peak component acceleration (PCA) demands were quantified based on the floor response spectrum (FRS) method without considering dynamic interaction effects. This study evaluated the main factors that influence the amplification or decrease of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 19 publications
3
34
0
1
Order By: Relevance
“…This outcome is consistent with findings reported in [23,24]. In other words, it can be concluded that with increasing ground motion intensity the related increase of the median PFA demand is quite low when the yield strength is exceeded.…”
Section: Applicationsupporting
confidence: 93%
“…This outcome is consistent with findings reported in [23,24]. In other words, it can be concluded that with increasing ground motion intensity the related increase of the median PFA demand is quite low when the yield strength is exceeded.…”
Section: Applicationsupporting
confidence: 93%
“… When certain conditions are met: (components with damping ratios smaller than 5% located near the bottom of the supporting structure with periods in the vicinity of higher modal periods of the supporting structure), inelasticity in the primary structure can increase the magnitude of component acceleration demands and component amplification factors (Sankaranarayanan and Medina, 2007;Chauduri and Villaverde, 2008;Medina et al, 2009). ASCE/SEI 7-16 Eq.…”
Section: -15mentioning
confidence: 99%
“…La última observación coincide con lo observado para las demandas de aceleración en sistemas con base rígida en términos de la poca efectividad que tiene la disipación de energía para reducir la contribución de la respuesta de modos superiores (Rodríguez et al 2007, Dowell et al 2008, Clayton y Medina 2010. Es importante hacer notar que el incremento en la rigidez lateral de la super-estructura, relativa a la del sistema de aislamiento, permite que un sistema complejo de múltiples grados de libertad (como los descritos por Medina et al 2006, Sankaranarayanan y Medina 2007, Clayton y Medina 2010, y Dowell et al 2008) exhiba un comportamiento similar al de un sistema de un grado de libertad con un solo pico de respuesta en el espectro de piso (como el descrito por Lin y Mahin 1985, Igusa 1990). Otra manera de caracterizar la amplificación de aceleración en un sistema aislado es a través de un cociente de aceleraciones:…”
Section: Dominio En El Tiempounclassified